Development of Flip book-Based Interactive Learning Media to Improving Understanding of Statistical Material Concepts - Siti Masrifah; Marhan Taufik; Adi Slamet Kusumawardana (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
This study aims to produce learning media that are practical and effective as well as to increase understanding of the concept of statistics material for class VIII students at Junior High School. The research method used the Research & Development (R&D) model with the concept of ADDIE (Analyst, Design, Development, Implementation and Evaluation. Data analysis techniques used validity tests, practicality tests, effectiveness tests and statistical tests t tests. The results showed that learning media were stated to be practical and effective based on student assessments with an average practicality result of 3.69 or 92% with very practical qualifications and could be used without revision and effectiveness test results with a value greater than 75% with an effective qualification used for Class VIII students. Furthermore, learning media was stated to be able to increase the understanding of statistical material concepts for Class VIII students which was shown statistically through a t test with a P value of 0.000<alpha 5% so that it was stated that learning media was able to increase students' understanding of statistical concepts.